Collecting the evidence: mechanistic insights into Akkermansia muciniphila’s impact on aging and systemic inflammation - Vorontsov, Aleksandr I.; Kruglov, Andrey A.; Gubernatorova, Ekaterina O. (Frontiers in Immunology, 2026)
Akkermansia muciniphila is a Gram-negative, mucin-degrading anaerobic bacterium that constitutes an important component of the human commensal microbiota. A reduction in its abundance is associated not only with intestinal barrier dysfunction but also with systemic inflammation and age-related metabolic disorders. Given its distinctive biological properties, A. muciniphila-based probiotics emerged as a promising strategy for alleviating age-associated metabolic and hematopoietic decline. Nonetheless, current experimental evidence is somewhat inconsistent. Accumulating data indicate that A. muciniphila can exert both beneficial and deleterious effects on systemic inflammation and tissue homeostasis, with outcomes strongly influenced by bacterial dose, host status, and the surrounding microbial and dietary context. While several studies report that A. muciniphila supplementation reinforces mucosal barrier integrity and mitigates chronic inflammation, thereby preserving bone marrow homeostasis; others describe deleterious effects, including mucus layer erosion and heightened metabolic endotoxemia. In this review, we summarize these findings and propose mechanistic explanations for how A. muciniphila may benefit the aging process, ultimately contributing to improved health and quality of life in the elderly population. Additionally, we identify key gaps in current knowledge and outline priorities for future mechanistic and longitudinal human studies needed to define when and how A. muciniphila-based interventions can be used safely and effectively during aging.